Dynamics of urban sprawl and sustainable development in China. (June 2020) - Wang, Xiaoxiao; Shi, Ruiting; Zhou, Ying
Abstract: Compared with the rich literature on urban sprawl in Western cities, relatively little is known of the driving factors, processes, and future trends of urban sprawl in China. This research analyzes the socioeconomic forces behind two parts of urban sprawl in China: urban decentralization and urban renewal, and reveals two basic characteristics of Chinese urban sprawl: de-densification and expansion of urbanized areas. It uses the term "urban sprawl" to consider the reasons behind urban transformation on a regional level in China. This research begins with definitions of sprawl in Western and Eastern countries, and follows with a dynamic analysis of the social, political, and cultural aspects of sprawl. Three case studies focus on three urban regions in China: Beijing, Shanghai, and Guangzhou. This research provides a comprehensive definition of "urban sprawl" in China, identifies the patterns of urban sprawl and growth, and indicates possible alternative strategies for urban expansion. Finally, it offers suggestions on how to effectively control urban sprawl in China, and provides a pathway to achieving sustainable development. Highlights: This research begins with definitions of sprawl in Western and Eastern countries, and follows with a dynamic analysis of the social, political, and cultural factors of sprawl. Then, three case studies focus on three urban centers in China: Beijing, Shanghai, and Guangzhou. Providing definitions of urban sprawl and Illustrating possible dynamic strategies for green urban growth in China. Finally, it will offer suggestions on how to effectively control urban sprawl in China, as well as provide a pathway to achieving sustainable development.